Familial amyotrophic lateral sclerosis in Alberta, Canada. Issue 4 (May 2013) - Pfister, Ted; Sekhon, Ramnik; White, Mitchell; Scott, Patrick; Munro, Susan; Johnston, Megan; Kalra, Sanjay; Korngut, Lawrence
Abstract: Systematic review data demonstrate that 5% of ALS cases are familial (FALS). Causative superoxide dismutase-1 (SOD1) mutations are identified in 10−20% of FALS. Few reports of FALS epidemiology exist in Canada. We completed a retrospective review of all FALS cases within the province of Alberta between 2002 and 2011. Descriptive summaries of genotypes identified and calculation of prevalences were performed. We reviewed 946 clinic database records and 49 subjects with FALS were identified (5.2%). Clinic charts for 47/49 were available and reviewed. Causative SOD1 mutations were observed in 17/47 (36%). The SOD1 I113T mutation was identified in 11/47 unrelated patients and was associated with a less variable survival than previously reported. The period and point prevalences of FALS in Alberta are approximately 2.05 per 100, 000 (95% CI 1.51−2.73) and 4.68 per 1, 000, 000 (95% CI 2.42−8.18), respectively. In conclusion, we report 47 cases of FALS in Alberta over the past decade. The proportion of SOD1-positive FALS cases is higher than reported elsewhere. The high proportion of I113T mutations is comparable to that previously observed in the adjacent province of British Columbia.